The role of aquaporins in the developing ovarian follicle - Williams, Leanne (2012)
The growth of ovarian follicles is well documented in terms of hormonal control, however the fluid dynamics of antral follicle growth is less well understood. Aquaporins (AQP) are transmembrane water channels which facilitate the passive movement of water. In mammals 13 AQPs have been identified in a vast range of tissue types. In terms of ovarian AQPs there is currently a paucity of information. Recent studies in rat, pig and human have revealed the presence of ovarian AQPs, but in doing so have also highlighted a lack of consensus on AQP-type and location.